THE MODERATING EFFECT OF COMPETITIVE STRATEGIES ON INTELECTUAL CAPITAL AND COMPANY VALUE IN BANKING COMPANIES - Rumini Rumini; Bambang Sugiharto; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
This research was conducted with the aim to determine the effect of Intellectual Capital on Corporate Values with Competitive Strategies in increasing and decreasing the relationship between Intleectual Capital and Corporate Value. Intellectull Capital in this study was measured using VAIC developed by Pulic. The sample in this study were 17 banking companies listed on (Indonesia Stock Exchange) IDX as much as 8 years.By using a simple regression analysis the results of the equation are obtained: Y = 0.201483 + 0.22356vaic + e . While the results of the T test obtained a T value with a probability of 0.0150, which means less than 0.05. The F test obtained an F value with a probability of 0.000154 <0.05. These results prove that the Intellectual Capital variable has a positive effect on Company Value. While the multiple linear equations obtained by the equation: Y = 1.471970 + 0.214295vaic + 0.4581455vaicsb + e. Based on these results Intellectual Capital gives a coefficient of 0.214295 with a probability value of 0.0013 <0.05, while Intellectual Capital with a Competitive Strategy gives a coefficient of 0.458145 with a probability of 0.0007 <0.05 means that Intellectual Capital has a positive effect on Corporate Values and Competitive Strategies can influence (strengthen) the relationship between Intellectual Capital with Corporate Value